On Passives with Goal or Beneficiary Arguments in Spanish - Carranza, Fernando Martín (2023)
Passivization in Spanish takes (active) clauses with a direct object and turns them into (passive) clauses in which that argument behaves as a subject. English allows secondary passives as well, in which the constituent that is promoted to the subject position is the goal or beneficiary argument of ditransitive predicates such as give: Peter was given a book. Although Spanish does not have this kind of passives, this paper discusses some data on ditransitive verbs whose passives allow the promotion of goal or beneficiary arguments. It is shown that there are at least two major types with differentiated characteristics: verbs that enable a construction we call beneficiary accusative and verbs that trigger what we call lexicalized goal-passives.